Middle Mesial Canal Identification and Endodontic Management of the Mandibular First Molar with Five Canals: A Case Report - Marita Anggaraini; Irmaleny Irmaleny (Maranatha Christian University, 2026)
Introduction: The middle mesial canal (MMC) is an anatomical variation occasionally encountered in mandibular first molars and often overlooked during endodontic treatment, potentially compromising clinical outcomes. This case report underscores the importance of recognizing and managing an MMC in five-canals mandibular molar. Methods: A 16-year-old male presented with lingering pain in the lower right posterior region. Clinical and radiographic findings led to a diagnosis of symptomatic irreversible pulpitis with symptomatic apical periodontitis in tooth #46. Canal exploration employed SLOB radiographic technique, magnification, ultrasonic troughing, and application of Krasner and Rankow’s laws. Five canal orifices were located—three in the mesial root, including a middle mesial canal, and two in the distal root. Canal preparation was achieved using Reciproc Blue instruments, coupled with passive ultrasonic irrigation for enhanced debridement. Obturation was performed with gutta-percha and a bioceramic sealer, chosen for its superior flowability and bioactivity. A full-coverage indirect overlay was placed to reinforce the remaining tooth structure. Results: At one-month follow-up, the patient reported complete resolution of symptoms, with radiographs showing well-obturated canals, intact periapical structures, and a functional restoration. Discussion: The presence of an MMC demands meticulous assessment and advanced visualization techniques. Knowledge of pulpal anatomy, effective instrumentation, and appropriate restorative choices are essential for long-term success. Conclusion: Successful endodontic outcomes depend on comprehensive canal identification, effective disinfection and obturation, and appropriate post-endodontic restoration.